Value Stocks versus Growth Stocks: An Examination of Bursa Malaysia - Rohuma, Hani (International Journal of Economics and Financial Issues, 2023)
The main objective of this research is to construct hypothetical value and growth portfolios and compare their performance on Bursa Malaysia over the examination period from 1 January 2006 to 1 January 2020 (168 months). This research also analyses whether there are differences in the performance between value and growth stocks in different sizes of the issuing company. Risk and return characteristics, risk-adjusted return, and the sample paired t-test are examples of statistical tests used in this research. The results emphasised that the average value premium over the examination period was 1%, and hence, the performance of growth and value stocks was broadly similar. When the capitalisation levels of issuing firms are taken into account, the results during the entire examination and the global financial crisis affirmed that the size effect exists only in the value category, while in the growth category, it does not exist. On the other hand, the value effect exists in the large-cap and small-cap categories. Besides, the value effect in small-cap stocks is higher compared to large-cap stocks. Finally, the results also demonstrate that value stocks have a significantly higher mean return than growth stocks at a level of 0.05, despite the firm's size.